2017
DOI: 10.1111/maps.12858
|View full text |Cite
|
Sign up to set email alerts
|

Unmelted cosmic metal particles in the Indian Ocean

Abstract: Fe-Ni metal is a common constituent of most meteorites and is an indicator of the thermal history of the respective meteorites, it is a diagnostic tool to distinguish between groups/subgroups of meteorites. In spite of over a million micrometeorites collected from various domains, reports of pure metallic particles among micrometeorites have been extremely rare. We report here the finding of a variety of cosmic metal particles such as kamacite, plessite, taenite, and Fe-Ni beads from deep-sea sediments of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
47
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(49 citation statements)
references
References 62 publications
1
47
0
Order By: Relevance
“…Genge and Van Ginneken also mention our sampling effort in Prasad et al (2013) where we reported ~5% of the total spherules to be either I-type or G-type and compare these with the abundances of the I-type and the G-type spherules which are close to 50% of the total collection thus implying that in the present area, a metal bolide had disrupted in the atmosphere to account for such large abundances of metals in the present study. We wish to clarify here that the samples used in Prasad et al (2013) and in Prasad et al (2017) are from the same geographic domains. The differences in the quantities of metallic particles between both the above methods of collection are because of the differences in the sampling methods employed in both these cases.…”
Section: Entry Heating Of Metallic Micrometeorites and Abundancesmentioning
confidence: 99%
See 2 more Smart Citations
“…Genge and Van Ginneken also mention our sampling effort in Prasad et al (2013) where we reported ~5% of the total spherules to be either I-type or G-type and compare these with the abundances of the I-type and the G-type spherules which are close to 50% of the total collection thus implying that in the present area, a metal bolide had disrupted in the atmosphere to account for such large abundances of metals in the present study. We wish to clarify here that the samples used in Prasad et al (2013) and in Prasad et al (2017) are from the same geographic domains. The differences in the quantities of metallic particles between both the above methods of collection are because of the differences in the sampling methods employed in both these cases.…”
Section: Entry Heating Of Metallic Micrometeorites and Abundancesmentioning
confidence: 99%
“…The MMs presented in our paper (fig. 6; Prasad et al 2017) have been plotted as they occurred. It is found that these MMs occur in different clusters defined by metallic minerals from different types of meteorites as presented by us in our fig.…”
Section: Chemical Evidence For Formation As Metal Micrometeoritesmentioning
confidence: 99%
See 1 more Smart Citation
“…The FeNi metal beads reported by Prasad et al (2017) show a much larger range of compositions than irregular grains and were suggested to form as (1) beads separated by immiscibility from chondritic objects during atmospheric entry, (2) unmelted spherical metal grains, or (3) the separated cores of metallic I-types. The compositions of the cores of Antarctic I-type spherules are shown in Fig.…”
Section: Chemical Evidence For Formation As Metal Micrometeoritesmentioning
confidence: 99%
“…The abundance of unmelted grains, therefore, would appear to be significantly larger than would be expected for low entry angle particles; however, a complete size distribution of I-type spherules as well as unmelted grains would be necessary to assess the degree of disparity. Prasad et al (2017) recognized that the large abundance of unmelted particles is not consistent with the entry heating of metal micrometeoroids. To reconcile the abundances, they suggested that metal grains could be liberated by fragmentation of larger dust particles at the top of the atmosphere causing deceleration and a decrease in heating.…”
Section: Introductionmentioning
confidence: 99%